Dry habitats were crucibles of domestication in the evolution of agriculture in ants. Issue 1852 (12th April 2017) - Branstetter, Michael G.; Ješovnik, Ana; Sosa-Calvo, Jeffrey; Lloyd, Michael W.; Faircloth, Brant C.; Brady, Seán G.; Schultz, Ted R.
Abstract : The evolution of ant agriculture, as practised by the fungus-farming 'attine' ants, is thought to have arisen in the wet rainforests of South America about 55–65 Ma. Most subsequent attine agricultural evolution, including the domestication event that produced the ancestor of higher attine cultivars, is likewise hypothesized to have occurred in South American rainforests. The 'out-of-the-rainforest' hypothesis, while generally accepted, has never been tested in a phylogenetic context. It also presents a problem for explaining how fungal domestication might have occurred, given that isolation from free-living populations is required. Here, we use phylogenomic data from ultra-conserved element (UCE) loci to reconstruct the evolutionary history of fungus-farming ants, reduce topological uncertainty, and identify the closest non-fungus-growing ant relative. Using the phylogeny we infer the history of attine agricultural systems, habitat preference and biogeography. Our results show that the out-of-the-rainforest hypothesis is correct with regard to the origin of attine ant agriculture; however, contrary to expectation, we find that the transition from lower to higher agriculture is very likely to have occurred in a seasonally dry habitat, inhospitable to the growth of free-living populations of attine fungal cultivars. We suggest that dry habitats favoured the isolation of attine cultivars over the evolutionary time spans necessary for domestication to occur.